INTRINSIC AND EXTRINSIC MOTIVATIONAL ORIENTATIONS FOR LEARNING ENGLISH: AFTER-SCHOOL ACTIVITIES AND ACADEMIC ACHIEVEMENT - Putri, Herlinda (2016)
This study aims to investigate students' motivation for learning English, in relation with after-school programs and activities, towards their academic achievement. Three types of data used were from survey (after-school programs), motivational questionnaires, and two types of interview (individual and focus-group interview). Data of survey and questionnaire were analyzed by grouping them into a diagram and tables, to explain overall results. Data of interviews were analyzed by transcribing them into literature-review related description. It was found that the students tend to have more extrinsic motivational orientation that they learn English as a compulsory subject. The study also found that non school-related activities may affect students' motivation for learning English, including their academic achievement. It can finally be concluded that teacher should help students to realize their motivation so they can foster it to achieve better academic outcomes.;-- Studi ini bertujuan untuk menginvestigasi motivasi siswa dalam belajar bahasa Inggris, dan kaitannya dengan program dan kegiatan setelah sekolah terhadap pencapaian academik mereka. Penelitian ini menggunakan tiga jenis data yang berasal dari survey (program setelah sekolah), kuisioner motivasi, dan wawancara (perorangan dan kelompok). Data dari survey dan kuisioner dianalisis dengan cara dikelompokan dalam diagram dan tabel, untuk menjelaskan keseluruhan hasil yang diperoleh. Data wawancara dianalisis dengan cara menuliskannya menjadi deskripsi yang dikaitkan dengan ulasan pustaka. Penelitian menunjukkan bahwa para siswa cenderung lebih memiliki orientasi motivasi ekstrinsik yaitu mereka belajar bahasa Inggris karena merupakan mata pelajaran wajib. Selain itu, aktivitas setelah sekolah yang tidak berkaitan dengan sekolah dapat memengaruhi motivasi mereka untuk mempelajari bahasa Inggris, termasuk memengaruhi pencapaian akademis mereka. Dapat disimpulkan bahwa guru sebaiknya membantu siswa menyadari motivasinya masing-masing, sehingga mereka dapat meningkatkan motivasi untuk mencapai hasil pembelajaran yang lebih baik.